1996
DOI: 10.1006/jmbi.1996.0611
|View full text |Cite
|
Sign up to set email alerts
|

The Transition from a Neutral-pH Double Helix to a Low-pH Triple Helix Induces a Conformational Switch in the CCCG Tetraloop Closing a Watson-Crick Stem

Abstract: The CCCG-loop in a DNA fragment, which is capable of forming an Structure, Design, and intramolecular triple helix as well as a hairpin structure, was investigated Synthesis, Laboratory of by NMR and molecular modeling studies. We used molecular modeling to lay the foundations for understanding 2300 RA Leiden the observed conformational switch. A lower amount of strain, related to The Netherlands the short C1'-C1' of the base-pair, and protonation effects of the structure comprising the Hoogsteen base-pair tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…As shown in fi gure 6, our structure could be shown to be explainable only in terms of a G:G(+) base pairing. As explained in the fi gure, it seems possible that the trans G:G H:W confi guration in conjunction with our trans G:G(+) H:S pair could act like a pH dependent conformational switch as in the case of the cis G:C W:W to cis G:C H:W switch discussed earlier (van Dongen et al 1996). It is also reasonable to suppose that the trans G:G(+) H:S confi guration which we have shown in fi gure 6 is the proper confi guration and the example we have chosen for computation is an intermediate for the switching process.…”
Section: Multimodality In Edge Interaction Possibilities Within a Paimentioning
confidence: 74%
See 1 more Smart Citation
“…As shown in fi gure 6, our structure could be shown to be explainable only in terms of a G:G(+) base pairing. As explained in the fi gure, it seems possible that the trans G:G H:W confi guration in conjunction with our trans G:G(+) H:S pair could act like a pH dependent conformational switch as in the case of the cis G:C W:W to cis G:C H:W switch discussed earlier (van Dongen et al 1996). It is also reasonable to suppose that the trans G:G(+) H:S confi guration which we have shown in fi gure 6 is the proper confi guration and the example we have chosen for computation is an intermediate for the switching process.…”
Section: Multimodality In Edge Interaction Possibilities Within a Paimentioning
confidence: 74%
“…Even when they do so, they would be constrained such that they cannot easily fl ip into forming canonical pairs, unless of course that is what is expected of them. For example, it has been reported that the transition from a neutral-pH double helix to a low-pH triple helix, involving a canonical G:C pair fl ipping to a hoogsteen C(+):G pair, induces a conformational switch in the CCCG tetraloop closing Watson-Crick stem (van Dongen et al 1996). With such specifi c functional and environmental constraints, it is not surprising that cis G: C(+) H:W base pair (system 26) was found to occur only four times in our database of 145 RNA structures (Das et al 2006), though the computed interaction energy of the base pairing was quite good .…”
Section: Occurrence Frequency Is Not a Function Of Energetics Of Basementioning
confidence: 99%
“…2B) when compared to those of random coils (À3.87 to À4.15 ppm) [23]. These unusual 31 P chemical shifts show the special backbone features of type II loop [16,24]. In addition, the unusually downfield H1 0 signals of C2 (6.45 ppm) and C6 (6.46 ppm), and the unusually upfield H1 0 signals of T3 (5.43 ppm) and T7 (5.64 ppm) (Fig.…”
Section: (Cctg) 2 Forms a Mini-dumbbell Structure Composed Of Two Ct mentioning
confidence: 85%
“…In addition to the two hydrogen bonds, the base stacked on top of the closing Hoogsteen base pair also contributes to the stability of the mini-loop [20]. Owing to the shorter interstrand C1 0 -C1 0 distance, the stacking interactions are more effective than those involving a closing Watson-Crick base pair [19,21]. In (TTTA) 3 , the base orientation of A8 also possesses the syn feature as evidenced by the similar NOE intensities of H8-H1 0 and H8-H2 0 /H2 00 (Fig.…”
Section: Resultsmentioning
confidence: 99%